1993
DOI: 10.1093/oxfordjournals.humrep.a138196
|View full text |Cite
|
Sign up to set email alerts
|

The effects on in-vitro fertilization of autoantibodies to spermatozoa in subfertile men

Abstract: Thirty-six infertile couples underwent treatment by in-vitro fertilization. In 16 couples (group 1) the male partner was positive for antisperm antibodies measured by direct mixed antiglobulin reaction, direct immunobead test, and serum and/or seminal plasma tray agglutination test. In 20 couples (group 2) the men had no such antibodies. Men with poor sperm motility were excluded. The female partners had no antisperm antibodies, and in the controls (group 2) infertility was due to a known female factor. The fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 9 publications
1
33
0
2
Order By: Relevance
“…Antisperm antibodies may have heterogeneous effects, depending on their cognate antigens [40]. They have been found to affect sperm motility [6,19], the acrosome reaction [8], penetration of cervical mucus [14], sperm binding to the zona pellucida [18], and sperm-egg fusion [9,42]. In addition, in the present study, sperm granulomas were histologically observed in 4 of 35 rats, and degenerated spermatids were found within the lumen of the cauda epididymis.…”
Section: Discussionsupporting
confidence: 48%
“…Antisperm antibodies may have heterogeneous effects, depending on their cognate antigens [40]. They have been found to affect sperm motility [6,19], the acrosome reaction [8], penetration of cervical mucus [14], sperm binding to the zona pellucida [18], and sperm-egg fusion [9,42]. In addition, in the present study, sperm granulomas were histologically observed in 4 of 35 rats, and degenerated spermatids were found within the lumen of the cauda epididymis.…”
Section: Discussionsupporting
confidence: 48%
“…6,29 Conventional in vitro fertilization (IVF) usually results in lower fertilization and cleavage rates in cases involving ASA-mediated infertility. 10,11,21,30 Intracytoplasmic sperm injection, on the other hand, has been shown to successfully overcome any deleterious effects of ASA. ICSI has yielded excellent results irrespective of the ASA levels, and results in fertilization rates, embryo development, and pregnancy rates similar to that which has been observed in other categories of male infertility.…”
Section: B Discussionmentioning
confidence: 99%
“…Indeed, when the degree of sperm autoimmunization was taken into account, it was always inversely correlated with the overall fertilization rate (130-132, and table 2). But, noteworthy, in some individual patients, a high fertilization rate was achieved even in the presence of a high degree of sperm autoimmunization (121,123,124,128).…”
Section: In Vitro Fertilization (Ivf) As Model Of Studymentioning
confidence: 99%
“…Table 2 shows the fertilization rates reported in series including couples with sperm autoimmunization in the male partner. In most reports the fertilization rate was significantly lower in the presence of sperm-bound antibodies than in the case of other indications for IVF (119)(120)(121)(122)(123)(124). However, in some other reports no significant difference was found (125-127).…”
Section: Interference With the Fertilization Processmentioning
confidence: 99%
See 1 more Smart Citation